Fixed point theorems on certain class of contractive mappings (1988)
The objective of this paper is to introduce the concepts of a H-contractive mapping and a π -ultimately contractive mapping on cartesian product of two metric spaces, and to show that, under certain restrictions, such mappings have a fixed point.